Plasma anti‐BIRC5 IgG may be a useful marker for evaluating the prognosis of nonsmall cell lung cancer - Zhao, Huan; Zhang, Xuan; Han, Zhifeng; Wang, Zhenqi; Wang, Yao (FEBS open bio, 2018)
A recent study demonstrated that circulating levels of IgG antibodies against linear peptide antigens derived from baculoviral IAP repeat‐containing protein 5 isoform 2 (BIRC5) and myc proto‐oncogene protein (MYC) were significantly increased in nonsmall cell lung cancer (NSCLC). This study was undertaken to replicate this initial work in an independent sample. An enzyme‐linked immunosorbent assay (ELISA) was developed in‐house to examine plasma IgG antibodies for three linear peptide antigens derived from BIRC5a, BIRC5b, and MYC in 211 patients with NSCLC and 200 control subjects. A Mann–Whitney U‐test demonstrated that plasma anti‐BIRC5a IgG levels, but not anti‐BIRC5b or anti‐MYC IgG levels, were significantly higher in NSCLC patients than control subjects, especially in male patients. Both squamous cell cancer and adenocarcinoma showed increased anti‐BIRC5a IgG levels, but the IgG levels were not found to be changed significantly in the early stage of NSCLC. Kaplan–Meier survival analysis showed that NSCLC patients with high anti‐BIRC5b IgG levels had better prognosis and longer overall survival (OS) than patients with low anti‐BIRC5b IgG levels, although this significant difference failed to survive the adjustment for age, gender, NSCLC stages, and types. Plasma anti‐BIRC5a and MYC IgG levels did not show significant associations with OS. In conclusion, Plasma anti‐BIRC5 IgG may be a useful marker for assessment of prognosis of NSCLC but not for early diagnosis of this malignancy. The high mortality rate of lung cancer is largely attributable to late diagnosis. This study aimed to verify claims that changes of plasma IgG levels against BIRC5 and MYC were associated with prognosis of nonsmall cell lung cancer (NSCLC). The results revealed that NSCLC patients with high anti‐BIRC5b IgG levels had longer survival than those with low anti‐BIRC5b IgG levels. This finding suggests that plasma anti‐BIRC5b IgG may have a prognostic value for patients with NSCLC.